ALTERING THE USE OF AGRICULTURAL INTO CONSTRUCTION LAND - PRACTICE AND TRENDS - Počuča, Milan; Drašković, Bojana (Economics of Agriculture, 2015)
Preservation of agricultural land as an imperative of prosperity of agriculture of the Republic of Serbia needs to be observed through causal questions as well, such as change of purpose of agricultural land into construction land, which is necessarily followed by conversion, a decade-long problem. Insuffciently resolved current questions of the aforementioned within legislative framework open up the possibility for improper use and exploitation of agricultural land. It is necessary to regulate the issue of conversion of construction land by legislative regulations i.e. altering use rights into property rights on construction land, and by doing so, open the way to investments in the Republic of Serbia. With the analysis of the effects of conversion and the adoption of a special law on this issue, construction activity would further prosper. The aim of this paper is to assess adequately the current problems of consumption, preservation and actual implementation of transferring agricultural land to construction land, with a view of the facts, practices and tendencies.